منظّمة الأمم المتّحدة بين الحاجة إلى الإصلاح والتحديات والمعوقات في ظل التحولات الراهنة - يورفلي خضر; هرمز نور الدين; قنوع صقر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
أصبحت الدعوة إلى تعديل وإصلاح النّظام الدولي الذي أنشأ الأمم المتّحدة مطلباً ملحاً من الدول الأعضاء، وذلك عبر قواعد قانونية دوليّة جديدة للتغلّب على حالة الجمود والشلل في أجهزة الأمم المتّحدة، وذلك عبر تفعيل بنود الميثاق التأسيسي للمنظمة التي ظلت معطلة لأكثر من نصف قرن مما انعكس على دور هذه المنظمة وإخفاقها في حفظ الأمن والسلم الدوليين نتيجة تحكّم القوى الكبرى الفاعلة في النظام الدولي بقرارات وأجهزة المنظمة، وخصوصاً مجلس الأمن. وبناءً على ما سبق سنعمل على دراسة واقع ومستقبل الأمم المتحدة في ظل المتغيرات التي يعرفها النظام الدولي، وكيف يمكن للمنظمة أن تستجيب وتتأقلم مع هذه المتغيرات وتواكب التحديات المطروحة أمامها، وتكون في مستوى تطلعات المجتمع الدولي بحسب ما جاء في ميثاقها التأسيسي. The call for the amendment and reform of the international system which established the United Nations has become an urgent demand of the Member States through a new set of international legal norms to overcome the stalemate and paralysis in the United Nations bodies and through activating the founding charter of the organization, which has been defunct for more than half a century, the thing that negatively affected the role of these bodies and lead to its failure in keeping international peace and security due to the control exercised by the superpowers on the international system and the decisions taken by the organization, especially in the Security Council. Based on the above, we will study the reality and the future of the United Nations in the light of the changes offered by the international system and how the organization can respond and adapt to these changes and keep up to the challenges ahead of it and be in the level of expectations of the international community, according to the statements in its Constitution.